Structural modification of aspirin to design a new potential cyclooxygenase (COX-2) inhibitors - Uzzaman, Monir (In Silico Pharmacol, 2020)
Aspirin (Asp) is one of the most important and ancient member of nonsteroidal anti-inflammatory drugs (NSAID), commonly used in medication of fever, pain and inflammation. It can inhibit the synthesis of prostaglandin by blocking the cyclooxygenase (COX). Attempts have been taken to analyze aspirin together with some of its modified derivatives applying quantum mechanical calculations in order to compare their physicochemical and biochemical properties. Density functional theory (DFT) with B3LYP/6-31G (d, p) basis set has been employed to elucidate their thermal, molecular orbital, equilibrium geometrical properties in gas phase. Molecular docking and nonbonding interactions have been performed against human cyclooxygenase-2 protein 5F1A to investigate the binding affinity and mode(s) of newly designed aspirin derivatives. ADMET prediction has been utilized to compare the absorption, metabolism, and carcinogenic properties of new derivatives with parent drug (Asp). Thermal and geometrical results support the thermochemical stability and equilibrium geometry of all the structures. From the molecular docking simulation, most of the derivatives exhibited better binding affinity than parent drug (Asp) with the receptor protein (5F1A). ADMET prediction disclosed the improved pharmacokinetic properties with lower acute oral toxicity of some derivatives. Based on quantum chemical, molecular docking and ADMET analysis, this investigation can be useful to understand the physicochemical and biochemical/biological activities of Asp and its modified derivatives to search a new antipyretic analgesic drug. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s40203-020-0053-0) contains supplementary material, which is available to authorized users.